LANGUAGE FUNCTION IN THE QUEEN ELIZABETH II’S CHRISTMAS MESSAGE IN 1975 - Ida Ayu Made Puspani; Ketut Santi Indriani; Made Ayu Diah Prabandari (Universitas Warmadewa, 2024)
Language is an inseparable part of human life. Sometimes we have to organize and observe in such a way that we can enter every sphere of speech, because language has many different rules and function in each community of speech. This paper aims to identify and analyze the functions of language in one of Queen Elizabeth II speech – a Christmas Message in 1975. The data were collected from a speech video of Queen Elizabeth II on YouTube and the official script from Official Website of The Royal Family. The kind of data used in this study is qualitative data, which consist of 572 words of speech, analyzed using the qualitative descriptive: literary approach method. Based on the analysis it found that The Queen Elizabeth II’s using some Language Function in her speech, namely Instrumental, Regulatory, Interactional, Personal, Heuristic, Imaginative, and Representational Function. The most used function in her speech is a Personal Function.